2020
DOI: 10.3892/ol.2020.12073
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑150 suppresses p27<sup>Kip1</sup> expression and promotes cell proliferation in HeLa human cervical cancer cells

Abstract: MicroRNAs (miRNAs) exert critical roles in the majority of biological and pathological processes. Recent studies have associated miR-150 with a number of different cancer types. However, little is known about miR-150 targets in cervical cancer. In the present study, the HeLa human cervical cancer cell line was transfected with hsa-miR-150-5p mimics, hsa-miR-150-5p inhibitors or miRNA controls. miR-150 was predicted to bind the 3'untranslated region (3'UTR) of the CDKN1B gene, which encodes the cyclin-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…It is important to note that CKS1B can also be negatively regulated by other miRNAs. 24 For example, miR-520h has been shown to inhibit CKS1B overexpression, mitigating the inhibitory effects on PACA-2 cells’ viability, migration, as well as invasion following LINC00657 knockdown. Furthermore, miR-1258 has been identified as another miRNA that negatively regulates CKS1B expression, leading to the inhibition of colorectal cancer cell proliferation, migration, and tumorigenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that CKS1B can also be negatively regulated by other miRNAs. 24 For example, miR-520h has been shown to inhibit CKS1B overexpression, mitigating the inhibitory effects on PACA-2 cells’ viability, migration, as well as invasion following LINC00657 knockdown. Furthermore, miR-1258 has been identified as another miRNA that negatively regulates CKS1B expression, leading to the inhibition of colorectal cancer cell proliferation, migration, and tumorigenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous miRNAs with deleterious regulatory functions are situated upstream of mRNAs and actively participate in the processes of tumorigenesis and tumor development. [22][23][24] In this study, a specific miRNA, has-miR-150-5p, was identified through database analysis as a negative regulator of CKS1B. This miRNA has previously been linked to the advancement of nasopharyngeal and cervical cancers by suppressing PYCR1 and p27 Kip1's expression.…”
mentioning
confidence: 94%
“…In addition, a screening of differentially expressed miRNAs in gastric cancer showed hsa-miR-148a-3p, hsa-miR-148b-3p, and hsa-miR-363-3p as having the greatest number of target genes, three microRNAs were significantly overrepresented in numerous cancer-related pathways, including the “Wnt signaling route,” the “MAPK signaling pathway,” and the “Jak-STAT signaling pathway” ( Luo et al, 2015 ). Overexpression of hsa-miR-150-5p accelerated the passage of human cervical cancer cells from G0/G1 to S phase, resulting in a considerable increase in cell proliferation ( Oboshi et al, 2020 ). In addition, the overexpression of hsa-miR-150-5p was linked to an increased risk of Chronic lymphocytic leukemia ( Casabonne et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The GSEA analysis also revealed that several oncogenic pathways were down-regulated in the case of high expression of miR-150. Although miR-150-5p acts as oncogene in some cancers [6,[36][37][38], miR-150-5p has mostly been show to play an anti-tumor role in cancer [5,[39][40][41][42][43][44][45][46][47]. The different roles of miR-150-5p in different studies and cancer types might depend on the target gene it regulates.…”
Section: Discussionmentioning
confidence: 99%